PENDAMPINGAN KADER GAPOKTAN DALAM KOMUNIKASI PELAPORAN TANGGAP DARURAT TERHADAP KEJADIAN KEGAWATAN SEHARI-HARI DI AREA PERTANIAN - Fibriansari, Rizeki Dwi; Maisyaroh, Arista; Widianto, Eko Prasetya (Jurnal Hasil Pengabdian kepada Masyarakat Universitas Jember, 2023)
Daily emergencies happen all around us. The Indonesian people in general have not been well socialized when responding to life-threatening events, both in terms of reporting techniques, initial handling and transportation methods, increasing the risk of death or experiencing complications due to late or mishandling at the beginning of the incident. So that group-based mentoring is needed to be able to effectively train and teach the community the right methods and techniques. One of the groups of people who are prone to emergencies is the farmer group, because of the high risk of emergencies related to the work of farmers in agricultural areas. Assistance to community groups through Gapoktan (Farmer Group Association) meetings which are held regularly every month, so we provide assistance for the formation of Gapoktan cadres in Jatiroto District to be empowered in their groups in reducing the risk of emergencies due to trauma and illness due to work in the agricultural area. This activity is carried out through a series of assistance stages, starting from how the initial response, reporting techniques, asking for emergency assistance and first aid techniques to evacuation techniques to be moved to a health service place. Through the collaboration between the research group, Faculty of Nursing, University of Jember and the Agriculture and Health Office of Lumajang Regency, we provide assistance to Gapoktan Jatiroto District, Lumajang Regency. Assistance for the introduction of emergencies that threaten death due to accidents and occupational diseases as well as methods of reporting communication to PSC Si Lugas 119 Lumajang Regency. After mentoring is carried out, there is an increase in the ability of farmers to recognize and report emergencies, it is hoped that with community service, this Gapoktan assistance can reduce the risk of emergencies due to trauma and diseases due to work in the agricultural area.